Does long‐term use of proton pump inhibitors cause vitamin B12 deficiency?. Issue 10 (October 2017) - Dela Cruz, Mark T.; Patel, Sohil; Ngo, Lynn; Sullivan, Kevin
Abstract : EVIDENCE‐BASED ANSWER : Vitamin B12 deficiency is associated with either longterm proton pump inhibitor (PPI) or histamine‐2 receptor blocker (H2 blocker) use, but a causal relationship is not established (SOR: B, meta‐analysis of high‐quality casecontrol studies).